Manfaat Pendidikan Kesehatan terhadap Konsistensi Penggunaan Kondom pada Pasien ODHA - Jamilah, Mimi; Yona, Sri (Journal of Telenursing (JOTING), 2024)
This study aims to see the effect of health education on the consistency of condom use in patients living with HIV. The method used in this writing is a systematic review through several databases, namely Pubmed, Proquest, Science Direct, Sage journals, ClinicalKey Nursing, and Ebsco. Article analysis process using PRISMA method. The results showed that health education provided to PLHIV can influence consistent condom use. Health education provided in person or over the phone can improve the knowledge and self-efficacy of PLHIV about the importance of condom use consistency. In addition, consistent condom use can prevent the transmission of diseases due to unsafe sexual intercourse. In conclusion, consistent condom use among PLWHA can prevent cross infection of the HIV virus and can prevent sexually transmitted infections (STIs). Keywords: HIV/AIDS, Health Education, Condom Use